EFEK KONSELING GIZI TERHADAP KUALITAS DIET PASIEN DIABETES MELLITUS TIPE 2 DI RSUP DR. SARDJITO YOGYAKARTA - , STEFANIA WIDYA SETYANINGTYAS; , dr.Lutfan Budi Purnomo, Sp.PD, K-EMD. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Introduction: One of key factor in diabetes mellitus management is improvement of diet quality. Nutrition counseling is one of medical nutritional therapy that is given in order to improve dietary pattern and lifestyle in patients with diabetes mellitus. Objective: This research wants to assess the effect of both individual and group counseling to improve diet quality in patient with diabetes mellitus. Method: This research uses quasi-experiment method with non-randomized control group pretest-posttest design. The diet quality of 54 respondens with diabetes mellitus was explored using semi quantitative food frequency questionnaire (sq-FFQ) before converted to diet quality score using Healthy Eating Index standard scores. Intervention group was given individual nutrition counseling first. Then they were formed into a group consists of 2 to 5 subjects per group to do focus group discussion. Every week, intervention group subjects will be monitored via telephone or sms. In fourth week, the diet quality of both control and intervention group will be re-evaluated. Result: Proportion of subjects that have adequate diet quality improved in intervention group (p=0,0235) after receiving individual and group counseling. In the other hand, diet quality in control group tended to decrease (p=0,0339) in the end of the research. The effectiveness of nutrition counseling in improving HEI scores is 73%. Conclusion: the combination of individual and group counseling can improve the diet quality in patient with diabetes mellitus.